2004
DOI: 10.4049/jimmunol.173.11.7003
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Activation in Airways Modulates Allergic Inflammation but Not Hyperresponsiveness

Abstract: Airways display robust NF-κB activation and represent targets for anti-inflammatory asthma therapies, but the functional importance of NF-κB activation in airway epithelium remains enigmatic. Therefore, transgenic mice were created in which NF-κB activation is repressed specifically in airways (CC10-IκBαSR mice). In response to inhaled Ag, transgenic mice demonstrated significantly ameliorated inflammation, reduced levels of chemokines, T cell cytokines, mucus cell metaplasia, and circulating IgE compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
147
3
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 148 publications
(162 citation statements)
references
References 54 publications
10
147
3
2
Order By: Relevance
“…Poynter et al reported that NF-kB repression selectively in airway epithelium significantly reduced the lymphocytes and eosinophils as well as eotaxin and IL-5 in BAL but did not alter AHR in a mouse model of asthma [29]. The dissociation between the number of inflammatory cells in BAL and AHR is consistent with our data and Poynter et al proposed the possibility of alternative signaling pathways, residual NF-kB activity and residual inflammatory cells in the lungs to account for the apparent lack of effect of absent epithelial NF-kB activity on AHR [29]. Although NF-kB appeared to be activated in our study it did not seem to be altered by EGFR inhibition in lung tissue as assessed by Western analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poynter et al reported that NF-kB repression selectively in airway epithelium significantly reduced the lymphocytes and eosinophils as well as eotaxin and IL-5 in BAL but did not alter AHR in a mouse model of asthma [29]. The dissociation between the number of inflammatory cells in BAL and AHR is consistent with our data and Poynter et al proposed the possibility of alternative signaling pathways, residual NF-kB activity and residual inflammatory cells in the lungs to account for the apparent lack of effect of absent epithelial NF-kB activity on AHR [29]. Although NF-kB appeared to be activated in our study it did not seem to be altered by EGFR inhibition in lung tissue as assessed by Western analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The production of eotaxin has also been reported to be mediated through NF-kB activation in a mouse model of allergic inflammation [28] and thus, in our study the blockade of the EGFR pathway could potentially have resulted from suppression of NF-kB activation followed by the reductions of IL-6, CINC-1 and eotaxin in BAL. Poynter et al reported that NF-kB repression selectively in airway epithelium significantly reduced the lymphocytes and eosinophils as well as eotaxin and IL-5 in BAL but did not alter AHR in a mouse model of asthma [29]. The dissociation between the number of inflammatory cells in BAL and AHR is consistent with our data and Poynter et al proposed the possibility of alternative signaling pathways, residual NF-kB activity and residual inflammatory cells in the lungs to account for the apparent lack of effect of absent epithelial NF-kB activity on AHR [29].…”
mentioning
confidence: 99%
“…For example, IL-6 (11) and IL-8 (12)/MIP-2 (13), two putative mediators of inflammation and fibrogenesis in lung, have NF-B binding sequences in their promoter regions that are critical to their transcriptional activation. NF-B is also linked to increased cell survival and may govern proliferative responses after stress (14).…”
mentioning
confidence: 99%
“…To test this hypothesis, we created a transgenic (Tg) mouse expressing an I B␣ mutant (also referred to as an I B␣ superrepressor) resistant to phosphorylation-induced degradation and under transcriptional control of the CC10 promoter to inhibit NF-B selectively in airway epithelial cells. The CC10-I B␣sr mice, as previously characterized (14,16), were then bred into the C57BL/6 background and evaluated in a murine inhalation model of chrysotile asbestos-induced fibrogenesis at time points of peak epithelial cell proliferation, inflammation and fibrogenesis, i.e., 3, 9, and 40 days, respectively (4,5). Based on results with CC10-I B␣sr mice after intranasal instillation of LPS (16) and in the OVA sensitization and challenge model (14), we hypothesized that acute inflammation in response to asbestos would be curtailed.…”
mentioning
confidence: 99%
See 1 more Smart Citation